Rancang Bangun Otomasi Mesin Sangrai Berbasis Arduino Uno Guna Meningkatkan Kualitas Fisik dan Cita Rasa Mutu Kopi di PDP Kahyangan Jember - Adhima Adhamatika; Aulia Brilliantina; Elok Kurnia Novita Sari; Dimas Triardianto (AGROSAINTIFIKA, 2023)
Jember Regency is one of the largest coffee producing regions in East Java with productivity reaching 11,859 kg/ha in 2020. One of the robusta coffee producers in Jember Regency is Perumda Perkebunan Kahyangan. Coffee production produced by Perumda Perkebunan Kahyangan is still at grade three. One of the causes of less than optimal production results is the lack of temperature control in the roasting process. The roasting process determines the taste of coffee. This is due to the chemical changes that occur in the coffee bean. Chemical changes occur due to loss of dry weight, especially CO2 gas and pyrolysis process occurs. Therefore this study aims to design a roasting temperature control device using the Arduino Promini microcontroller and a thermocouple sensor as a temperature sensor. There are four stages carried out in the design of automation on the roaster machine, namely: the design stage is carried out with four stages, namely hardware and software design, the implementation stage of the automated device system on the roaster machine, the data collection stage, and the data collection stage.